Kuhn and coherentist epistemology - Šešelja, Dunja; Straßer, Christian (Studies in history and philosophy of science, 2009)
The paper challenges a recent attempt by Jouni-Matti Kuukkanen to show that since Thomas Kuhns philosophical standpoint can be incorporated into coherentist epistemology, it does not necessarily lead to: (Thesis 1) an abandonment of rationality and rational interparadigm theory comparison, nor to (Thesis 2) an abandonment of convergent realism. Leaving aside the interpretation of Kuhn as a coherentist, we will show that Kuukkanens first thesis is not sufficiently explicated, while the second one entirely fails. With regard to Thesis 1, we argue that Kuhns view on inter-paradigm theory comparison allows only for (what we shall dub as) the weak notion of rationality, and that Kuukkanens argument is thus acceptable only in view of such a notion. With regard to Thesis 2, we show that even if we interpret Kuhn as a coherentist, his philosophical standpoint cannot be seen as compatible with convergent realism since Kuhns argument against it is not ultimately empirical, as Kuukkanen takes it to be.